Divergent responses of wetland methane emissions to elevated atmospheric CO2 dependent on water table. (15th October 2021) - Lin, Yongxin; Yuan, Junji; Liu, Deyan; Kang, Hojeong; Freeman, Chris; Hu, Hang-Wei; Ye, Guiping; Ding, Weixin
Highlights: Elevated CO2 increases CH4 emissions in an intermittently inundated marsh. Elevated CO2 decreases CH4 emissions in a persistently inundated marsh. Response of CH4 emissions to elevated CO2 is determined by hydrology and vegetation. CH4 emissions from wetlands under elevated CO2 may have been grossly overestimated. Abstract: Elevated atmospheric CO2 may have consequences for methane (CH4 ) emissions from wetlands, yet the magnitude and direction remain unpredictable, because the associated mechanisms have not been fully investigated. Here, we established an in situ macrocosm experiment to compare the effects of elevated CO2 (700 ppm) on the CH4 emissions from two wetlands: an intermittently inundated Calamagrostis angustifolia marsh and a permanently inundated Carex lasiocarpa marsh. The elevated CO2 increased CH4 emissions by 27.6–57.6% in the C. angustifolia marsh, compared to a reduction of 18.7–23.5% in the C. lasiocarpa marsh. The CO2 -induced increase in CH4 emissions from the C. angustifolia marsh was paralleled with (1) increased dissolved organic carbon (DOC) released from plant photosynthesis and (2) reduced (rate of) CH4 oxidation due to a putative shift in methanotrophic community composition. In contrast, the CO2 -induced decrease in CH4 emissions from the C. lasiocarpa marsh was associated with the increases in soil redox potential and pmoA gene abundance. We synthesized data from worldwide wetland ecosystems, and found that the responses of CH4 emissions to elevated CO2 was determined by the wetland water table levels and associated plant oxygen secretion capacity. In conditions with elevated CO2, plants with a high oxygen secretion capacity suppress CH4 emissions while plants with low oxygen secretion capacity stimulate CH4 emissions; both effects are mediated via a feedback loop involving shifts in activities of methanogens and methanotrophs. Graphical abstract: Image, graphical abstract